Tahapan Perubahan Perilaku Pecandu Narkoba Di Yayasan Sakinah Harakah Bhakti, Tangerang Selatan - Khoerisa Rizkia; Sokhivah Sokhivah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Changes in the behavior of drug users have a negative impact if the substance enters the user's body. So that the addictive behavior must be. This research was conducted at the Sakinah Harakah Bhakti Foundation, South Tangerang, to help addicts gradually change their addictive behavior using an eclectic approach, namely combining various therapeutic methods such as MI, CBT, and 12 steps of recovery. This study used a qualitative method with a purposive sampling technique in selecting informants. The results in this study indicate that changes in the behavior of clients undergoing rehabilitation occur in the ready to change phase, namely from the preparation stage to action using CBT therapy through topic sessions and 12 steps through JFT meetings. As for the initial phase when the client is still not ready to change, namely precontemplation using MI therapy through giving affirmations; and when the client starts to become aware but doesn't want to change yet, namely contemplation through giving MI open questions; the maintenance phase uses 12 steps through follow-up instructions regarding NA; and the ending phase of termination using MI through providing motivation when the client has successfully undergone a series of therapies.